Stack Pinning of Long Bone Fractures: A Retrospective Study - Gibson, Karen L.; vanEe, R. T. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Long bone fractures in 20 dogs and five cats were repaired using a stack pinning (multiple intramedullary pins) technique. These cases were evaluated with long-term radiographic and physical examination. Factors including fracture location, age of animal, fracture reduction, and percent of medullary cavity filled by intramedullary pins were noted to assess their effect on postoperative complications. Specifically, distal long bone fractures had a greater tendency to develop complications than did mid-shaft or proximal fractures (p = 0.10). Other factors were not found to significantly increase the potential for fracture related complications. The overall complication rate associated with this method of fracture repair was greater than 50%. External fixators or plates were judged necessary to improve fracture stability at initial or subsequent operations in 44% of cases. Stack pinning was found to be an unreliable method of repair for long bone fractures in this clinical study.
Keywords: Fracture; intramedullary pins